Phonetic characteristics of vocalizations during pain - Lautenbacher, Stefan (Pain Rep, 2017)
INTRODUCTION AND OBJECTIVES: There have, yet, been only few attempts to phonetically characterize the vocalizations of pain, although there is wide agreement that moaning, groaning, or other nonverbal utterance can be indicative of pain. We studied the production of vowels “u,” “a,” “i”, and “schwa” (central vowel, sounding like a darker “e” as in hesitations like “ehm”)—as experimental approximations to natural vocalizations. METHODS: In 50 students vowel production and self-report ratings were assessed during painful and nonpainful heat stimulation (hot water immersion) as well as during baseline (no-stimulation). The phonetic parameters extracted were pitch (mean F(0)), phonatory fluctuations (range F(0)) and loudness (acoustic energy level). RESULTS: Only for the vowels “u” and “schwa,” which might be considered best approximations to moaning and groaning, did pitch and loudness increase during pain. Furthermore, changes from nonpainful to painful stimulations in these parameters also significantly predicted concurrent changes in pain ratings. CONCLUSION: Vocalization characteristics of pain seem to be best described by an increase in pitch and in loudness. Future studies using more specific and comprehensive phonetic analyses will surely help to provide an even more precise characterization of vocalizations because of pain.